QAR: Strategy implementation for reading comprehension of recount texts - Nira Erdiana; Usman Kasim; Nadia Juwita (Studies in English Language and Education, 2017)
The objective of this research is to find out whether QAR strategy is effective in reading comprehension of recount text. This research uses experimental research design. This research took place at Madrasah Tsanawiyah Negeri Model Banda Aceh. A second grade class was chosen as the research sample, which consisted of 36 students. The research instrument used to gather the data was a set of essay tests, which were divided to pre-test and post-test. The result of the research was analyzed by using paired t-test formula. The calculation result shows that the observed t value is less than t lower critical vaue in the t distribution table (-5.624 2.030) at the 0.05 level of significance with 35 degree of freedom. It means that null hypothesis (H0) is rejected, which proves that Question Answer Relationship strategy effectively improves the second grade students’ reading comprehension of recount text.